Case report: The diagnostic dilemma of indeterminate biliary strictures: report on two cases with a literature review - Meng, Chunyan; Wang, Jing; Zhang, Peipei; Wang, Bo (Frontiers in Oncology, 2024)
Background: It is still a challenging problem for clinicians to explore the nature of the indeterminate biliary strictures (IBSs). Approximately 20% of biliary strictures remain undetermined after a thorough preoperative assessment.Case presentation: Here, we present two cases of indeterminate biliary strictures patients, whose cross-sectional imaging and endoscopic examination were nondiagnostic. The patients underwent exploratory laparotomy finally and were confirmed as malignancy. We also reviewed the recent reports in literatures regarding the evaluation of IBSs.Conclusion: Given the majority of the biliary strictures are malignancy, preoperative differentiation between benign and malignant is critical for choosing the best therapeutic regimen. Thus, close follow-up, multiple multidisciplinary discussion, and prompt surgical exploration are necessary for some difficult diagnostic cases.